Clinico-mycological study of Dermatophytosis at a tertiary medical center of Uttar Pradesh - Dr. Sunil Kumar Gupta; Dr. Jitendra Prasad; Dr. R. B. Brahmane (Tropical Journal of Pathology and Microbiology, 2017)
Background: Now day’s number of dermatophyte infection in general population is increasing. It is generally known as Tinea corporis, Tinea cruris, Tinea faciei etc.Material and Methods: A prospective study was done to know the current clinical status of dermatophytic infection in patients attending the outpatient department of skin at a tertiary medical center. Mycological study of skin scraping was done in department of Microbiology. The data was interpreted by statics.Result: In the present study, most common age group affected 21-30 years with 37.90%. Male to female ratio was 4.7:1. Dermatophytoses infection was found to be higher among manual worker (40.1%) and in lower middle class (52% cases). Tinea corporis and Tinea cruris were the most common clinical type (48%). KOH positivity was seen in78.8% of cases.Conclusion: Dermatophyte infection is quite prevalent now days. It is more in middle age group with male preponderance. It is more commonly seen in lower middle class and mostly in manual workers. Tinea corporis et cruris is the commonest presentation.